Cirebon City Tourism Competitiveness for Tourism Economic Development - Elisabeth Kirana (Jurnal Indonesia Sosial Teknologi, 2025)
In the West Java Provincial Tourism Development Master Plan, Cirebon City is included in the Provincial Tourism Strategic Area (KSPP), with tourist attractions in the Cultural Heritage Area. The development of the tourism sector can generate jobs, equal income distribution, and community welfare. As a city that is one of the tourism development areas of West Java, and one of the cities that ranks 4th in the number of GDP according to Regencies/Cities in West Java, the focus of this research is on the competitive advantage of Cirebon City tourism in the province using the Tourism Competitiveness Index. By using eight tourism competitiveness indicators according to TTCI, including the Human Tourism Indicator, Price Competitiveness Indicator, Human Resources Indicator, Openness Indicator, Social Development Indicator, Infrastructure Development Indicator, Environment Indicator, and Technology Advancement Indicator. Using secondary data with quantitative descriptive analysis and comparative approaches, the competitive advantages of Cirebon City tourism will be known